Sistem Otomatisasi Hidroponik Budidaya Sayuran sebagai Upaya Pemberdayaan Mandiri Santri Pondok Pesantren Pacul Bojonegoro - Roihatur Rohmah; Muhammad Jauhar Vikri; Mula Agung Barata; Zakki Alawi; Moh. Muhajir; Vita Dwi Rahmawati; Rheyna Anggri Setyani (I-Com: Indonesian Community Journal, 2024)
Vegetables are a source of vitamins and fiber which are very beneficial for student growth. Vegetables can improve human brain performance. Students or santri who are in Islamic boarding schools generally consume minimal vegetables regularly. One of the Islamic boarding schools in the city of Bojonegoro. Community service activities in the form of hydroponic system training are needed by students with the aim of increasing students' knowledge of vegetable cultivation using hydroponics as an effort to empower students to independently consume vegetables. In the training activities that have been carried out, an automatic hydroponic system has been successfully created that uses a water level sensor in a DFT (Deep Flow Technique) pipe for irrigation. Service is carried out using the Rapid Rural Appraisal method and participatory learning and action. The results of the activities in this training were an increase in students' knowledge about hydroponics from 30% to 72%. Apart from that, there is also 1 hydroponic system dedicated to the Al Falah Islamic boarding school from the service team as a means of applying vegetable cultivation to meet the students' vegetable consumption needs.